2015
DOI: 10.1099/mic.0.083923-0
|View full text |Cite
|
Sign up to set email alerts
|

Galleria mellonella is an effective model to study Actinobacillus pleuropneumoniae infection

Abstract: Actinobacillus pleuropneumoniae is responsible for swine pleuropneumonia, a respiratory disease that causes significant global economic loss. Its virulence depends on many factors, such as capsular polysaccharides, RTX toxins and iron-acquisition systems. Analysis of virulence may require easy-to-use models that approximate mammalian infection and avoid ethical issues. Here, we investigate the potential use of the wax moth Galleria mellonella as an informative model for A. pleuropneumoniae infection. Genotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 55 publications
5
65
0
1
Order By: Relevance
“…Although the relevance of sRNAs in A. pleuropneumoniae pathogenesis is suggested by previous work with mutants for the sRNA molecular chaperone Hfq (Subashchandrabose et al 2013;Pereira et al 2015b), little information exists on abundance and possible roles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the relevance of sRNAs in A. pleuropneumoniae pathogenesis is suggested by previous work with mutants for the sRNA molecular chaperone Hfq (Subashchandrabose et al 2013;Pereira et al 2015b), little information exists on abundance and possible roles.…”
Section: Discussionmentioning
confidence: 99%
“…We envisage that the Arccs discovered in our study are negative regulators, although further experiments, e.g., comparative RNA-seq Most sRNAs have as targets mRNAs directly implicated in either virulence or stress resistance. Although this was partially expected given the aforementioned phenotypes of reduced biofilm-forming capacity, sensitivity to oxidative stress (Subashchandrabose et al 2013), and reduced virulence in an alternative infection model (Pereira et al 2015b) displayed by A. pleuropneumoniae mutants for the hfq gene, new candidates for virulence determinants were defined by the present regulatory network. Two categories of potential targets that are part of extremely important systems for the establishment of A. pleuropneumoniae as a pig pathogen, and thus strong mutant candidates for live attenuated vaccines, are the iron-acquisition systems and Apx toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to variations in infection dynamics. 13 High-virulence strain (GN0576) is able to grow within the host, while low-virulence strain (GN0690) is not able to. We found that killing of G. mellonella larvae depended on the number of bacteria inoculated.…”
mentioning
confidence: 99%
“…larvae over other invertebrate models is their ability to survive at 37 °C, the mammalian body temperature. 8,13 G. mellonella was used as a model system to study A. baumannii pathogenesis and therapeutics. 5 McLaughlin et al 14 quantified the clinical virulence of K. pneumoniae producing carbapenemase K. pneumoniae with a G. mellonella model.…”
mentioning
confidence: 99%